42‐3: An Anti‐bacteria and Anti‐virus Liquid Crystal Display - Meng, Xianqin; Li, Hu; Zhang, Yong; Xu, Xiaoling; Liu, Sha; Zhang, Douqing; Zheng, Liangliang; Wang, Dan; Liu, Zhiqiang (SID International Symposium Digest of technical papers, 2024)
Health is becoming an increasingly important indicator for displays, especially after suffering the CODIV‐19 in past years. This manuscript is reporting a novel anti‐bacteria and anti‐virus liquid crystals display which is using an optimized antibacterial and anti‐virus materials on displays with certain technical processes. The antibacterial ratio can reach to 99.99% for both Escherichia coli and Staphylococcus aureus. Moreover, its anti‐virus ratio can attain above 91.36% for H3N2 and 96.45% for H1N1 viruses, respectively. Its optical properties such as transmission and reflection are all quite similar as the one without antibacterial and anti‐virus treatment. This kind of technology can be used for touching and interacting displays, such as tablet personal computer, cellphones, as well as public interaction screens, and so on.